Production potential of Vanilla planifolia Jacks in Totonacapan, Mexico, using geographic techniques - Santillan, Alberto; Trejo Cabrera, Maryjose; Martínez Sánchez, Araceli; Martínez Ángel, Luis; Vásquez Bautista, Nehemías (Revista Mexicana de Ciencias Agrícolas, 2019)
The Totonacapan region, between the northern limits of Puebla and Veracruz, produces 80% of the vanilla in Mexico, and is considered the center of origin of the species Vanilla planifolia Jacks. However, the area sown has decreased, which affects the competitiveness of the sector. In the present work a socio-economic characterization of the producers of Vanilla planifolia Jacks was carried out during 2017 and 2018 and the productive potential for the cultivation in the Totonacapan region was determined through the use of geographic information systems (GIS) based on factors edaphoclimatic and physiographic. Results show that production is a secondary economic activity, among producers over 55 years of age and in a smallholder situation. The highest productive potential is located northwest of the Totonacapan region and is conditioned by the increase in rainfall in the driest month (April:
Keywords: maxent; maximum entropy; multicriteria evaluation; potential distribution